Aplikasi Monitoring Lokasi Anak Menggunakan Location Based Service Dengan History Tracking Lokasi Berbasis Android - Baharuddin, Shofi; Jatmika, Sunu (Institut Tekonologi dan Binisi Asia Malang, 2024)
This study discusses the problems of every parent because they have many activities or activities that cannot be avoided. This busyness reduces the supervision and monitoring of their children, making parent worry about the whereabouts of their child’s location. Because at the stage of growth and development of children aged 10 to 18 year they tend to be more interested in exploring things around them. Increased supervision and monitoring of children is needed without reducing children’s freedom to learn and explore their environment. For this reason, an application system is needed that can make it easier for parents to supervise and monitor the location of their children. One alternative way that allows monitoring of location presence and good accuracy is to use Location Based Service with location tracking history. Location Based Service is an information service that can be accessed using mobile devices through the internet and cellular networks that utilize the capabilities of location pointers (maps) on mobile devices. In measuring position, latitude and longtitude are used to determine geographic location. With a note the application must be planted on the smartphone of parents and children. This study produces an Android-based application that is used for monitoring the location of children using Location Based Service with location tracking history with the aim of displaying the child’s location and also tracking location history that can be accessed via the parent’s smartphone.